2010
DOI: 10.1117/12.866413
|View full text |Cite
|
Sign up to set email alerts
|

Best depth of focus on 22-nm logic wafers with less shot count

Abstract: The contact layer for the 22 nm logic node faces many technological hurdles. Even using techniques such as multipleexposure patterning and 193 nm immersion, it will be difficult to achieve the depth of focus and CD uniformity required for 22 nm production. Such difficulties can be mitigated by recent advances in Inverse Lithography Technology (ILT). For example, circular main features combined with complex curvilinear assist features can provide superior CD uniformity with the required depth of focus, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…MB-MDP as introduced in previous papers [10][11][12][13][14] combines shot count reduction by using overlapping shots and Mask Process Correction (MPC) in one step. Since MB-MDP simulates the resulting mask contour in a similar way that OPC does on the wafer level, MB-MDP enables the use of overlapping shots, dose modulation of individual e-beam shots and character projection.…”
Section: B Model-based Mask Data Preparation (Mb-mdp)mentioning
confidence: 99%
“…MB-MDP as introduced in previous papers [10][11][12][13][14] combines shot count reduction by using overlapping shots and Mask Process Correction (MPC) in one step. Since MB-MDP simulates the resulting mask contour in a similar way that OPC does on the wafer level, MB-MDP enables the use of overlapping shots, dose modulation of individual e-beam shots and character projection.…”
Section: B Model-based Mask Data Preparation (Mb-mdp)mentioning
confidence: 99%
“…Contact wafer targets with "curvy" assist features [3] are potentially well suited to the technique: exact matching of the assist feature shapes is not required and contact "main feature" shapes are faithfully represented by circles.…”
Section: Related Workmentioning
confidence: 99%
“…In 2010, D2S introduced the concept of using model-based mask data preparation (MB-MDP) that employs overlapping VSB shots to significantly reduce the curvilinear ILT mask shot count while improving dose margin. Fujimura et al 70,71 showed an ideal ILT mask pattern for 22-nm contact holes, with curvilinear patterns written with about the same number of shots as a simplified Manhattanized mask (Fig. 34).…”
Section: Overlapping Shots and Mask Simulation For Vsb Shot Count Reductionmentioning
confidence: 99%
“…Figure 38(a) shows an example contact array with curvilinear ILT for 193i producing desired curvilinear mask target shapes, then the VSB shots generated to produce it using overlapping shots. 70,71,119,120 In the figure, green lines show the wafer target, red lines show the wafer image simulated from mask images simulated from the VSB shots in a double simulation process. The VSB shots are shown as hatched blue rectangles.…”
Section: Overlapping Shots and Mask Wafer Co-optimization Solve The Vsb-written Ilt Mask Problemmentioning
confidence: 99%